Serving Time: Volunteer Work, Liminality and the Uses of Meaningfulness at Music Festivals - Laura Toraldo, Maria; Islam, Gazi; Mangia, Gianluigi (Journal of Management Studies, 2019)
AbstractDrawing from a participant‐observer study of volunteering in the context of UK music festivals, we examine how the sense of meaningfulness and community relate to instrumental goals of consumption and efficiency. We argue that the liminal nature of the festival setting supports an ambivalence in which meaningfulness is established through constructions of community, while the commodification of community feelings leads to heterogeneous understandings of the work setting. Our findings reveal heterogeneous ways in which work was rendered meaningful by festival volunteers, ranging from (1) A commodity frame, characterizing work as drudgery seeking ‘fun’ through consumption (2) A ‘communitas’ frame, emphasizing a transcendental sense of collective immediacy and (3) A cynical frame, where communitas discourse is used instrumentally by both managers and workers. We discuss meaningful work as caught between creative community and ideological mystification, and how alternative workspaces vacillate between emancipatory principles of solidarity and neo‐normative forms of ideological control.